Perbandingan Efektivitas Profilaksis Intermiten Klobazam Versus Diazepam pada Kejang Demam Sederhana (KDS): Systematic Review: Comparison Effectiveness of the Intermittent Prophylaxis of Clobazam Versus Diazepam in Simple Febrile Seizures (SFS): Systematic Review - Sulastri; Mutia Hariani Nurjanah; Melati Apriliana Ramadhani; Arif Santoso; Rahma Diyan Martha; Rissa Laila Vifta; Annisah Mahanani (Indonesian Journal of Pharmacy and Natural Product, 2024)
Febrile seizures are seizures that occur when body temperature rises (rectal temperature > 38o C). Each seizure can possibly cause epilepsy and trauma to the brain. The next priority is efforts to stop acute seizure attacks which can usually be treated with anti-seizure medication. Intermittent prophylaxis with clobazam at the onset of the first febrile seizure provides better results. This systematic review aims to review articles related to the use of intermittent prophylaxis of clobazam vs diazepam for children suffering from simple febrile seizures. The literature search method uses Google Scholar, PubMed and BMJ databases based on keywords. The selected articles were articles published between 2009-2023, full text in English, were original articles comparing the effectiveness of intermittent prophylaxis use of clobazam vs diazepam in febrile seizures in children. The results obtained were 4 articles that were relevant to the objectives of this systematic review. Data is homogeneous with RR of 0.44 (95% CI: 0.32-0.60) so that the therapeutic effectiveness of administering clobazam compared with diazepam is not significantly different even though there is a chance that the effectiveness of clobazam is 0.44 times compared with administering diazepam. The efficacy of clobazam compared to diazepam, clobazam has better advantages than diazepam in preventing recurrence of febrile seizures. Apart from that, the side effects that occur with clobazam are significantly lower, for example drowsiness and sedation. ABSTRAK Kejang demam merupakan bangkitan kejang yang terjadi pada kenaikan suhu tubuh (suhu rektal > 38o C). Setiap kejang kemungkinan dapat menimbulkan epilepsi dan trauma pada otak. Prioritas selanjutnya berupa usaha untuk menghentikan serangan kejang akut yang biasanya dapat ditangani dengan pemberian obat anti kejang. Pemberian profilaksis intermiten dengan klobazam pada permulaan terjadinya kejang demam pertama memberikan hasil yang lebih baik. Systematic review  ini bertujuan untuk mereview artikel-artikel terkait adanya penggunaan profilaksis intermiten klobazam vs diazepam untuk anak penderita kejang demam sederhana. Pencarian literatur menggunakan metode berupa database Google scholar,  PubMed dan BMJ berdasarkan keywords. Artikel yang dipilih adalah artikel yang dipublikasikan antara tahun 2009-2023, fulltext dalam inggris, merupakan original article yang membandingkan efektivitas antara penggunaan profilaksis intermiten klobazam vs diazepam pada kejang demam pada anak. Hasil diperoleh 4 artikel yang relevan terhadap tujuan systematic review ini. Data bersifat homogen dengan RR 0,44 (CI 95%: 0,32-0,60) sehingga efektivitas terapi pemberian klobazam dibandingkan dengan diazepam tidak berbeda bermakna meskipun terdapat peluang efektivitas klobazam sebesar 0,44 kali dibandingkan dengan pemberian diazepam. Kemanjuran klobazam dibandingkan dengan diazepam, klobazam memiliki keunggulan lebih baik dibandingkan diazepam dalam mencegah kekambuhan kejang demam. Selain itu efek samping yang timbul pada klobazam secara signifikan jauh lebih rendah misalnya seperti mengantuk dan sedasi.